ESTIMATED WEIGHT DIFFERENCE FORMULA FETAL JOHNSON WITH BABY BIRTH WEIGHT IN BPM BENIS JAYANTO - Siti .; Maryanti .; Putri Kusumawati Priyono (STIKES DUTAGAMA KLATEN, 2015)
Background : An estimated 90% of maternal deaths occur at the time of delivery and approximately 95% of the causes of maternal mortality are obstetric complications can not be predicted in advance. One way to prevent obstetric complications by knowing the estimated fetal weight by the formula Johnson. Johnson-Tohsach formula is one formula that is frequently used by midwives in knowing the estimated fetal weight. Determination of fetal weight estimates are accurate by comparing birth weight is difficult because there is no precise measuring instruments. Based on the results of the preliminary study dated December 7, 2013 obtained the data from the Independent Midwife Practice (BPM) Jayanto Benis Kujon Village, District Ceper, Klaten regency in the month of November 2013 there were 12 maternal birth weight babies have a greater than estimated fetal weight and the weight 5 babies are born smaller than the estimated fetal weight. Objective : To determine differences in the estimated weight of the fetus with birth weight Methods : The study was comperative study with cross sectional study design. Statistical test using paired t-test. The population in this study the entire maternity in March 2014. The sample in this study are all mothers who meet the inclusion and exclusion criteria. The sampling is total sampling with a sample of 34 mothers giving birth. RESULTS : Based on the data analysis by paired t-test p value = 0.00 (p <0.05) .The result of research is said to be significant. Which means that there is a difference between estimated fetal weight formula Johnson with birth weight. Conclusion : There is a difference in estimated fetal weight formula Johnson with birth weight.